Potential of using transcriptome sequencing data in choosing therapy for patients with colorectal cancer - S. V. Apalko; V. S. Shimansky; A. Kel; N. N. Sushentseva; N. V. Tyukavina; S. A. Kovalenko; S. G. Shcherbak (Кардиоваскулярная терапия и профилактика)
Aim. To study the applicability of RNA (ribonucleic acid) sequencing with master regulator identification for predicting the effectiveness of targeted therapy in patients with colorectal cancer.Materials and methods. Tissue samples from three patients with colorectal cancer obtained from postoperative material were used. All patients received palliative antitumor therapy in standard regimens in accordance with the tumor location and the status of RAS and BRAF gene mutations. The transcriptome of tumor and healthy tissue of each patient was sequenced, and master regulators in the tumor tissue were analyzed.Results. A list of master regulators was found for each patient and possible therapeutic agents most suitable for suppressing the tumor process were predicted.Conclusion. The potential of computer analysis of the molecular profile of colorectal adenocarcinoma in predicting the effectiveness of therapy is shown. However, to determine the clinical potential of this technique, a study on a wider sample is required.